Use of multispectral satellite datasets to improve ecological understanding of the distribution of Invasive Alien Plants in a water‐limited catchment, South Africa. (8th June 2020) - Mtengwana, Bhongolethu; Dube, Timothy; Mkunyana, Yonela P.; Mazvimavi, Dominic
Abstract: Invasive Alien Plants (IAPs) pose major threats to biodiversity, ecosystem functioning and services. The availability of moderate resolution satellite data (e.g. Sentinel‐2 Multispectral Instrument and Landsat‐8 Operational Land Imager) offers an opportunity to map and monitor the occurrence and spatial distribution of IAPs. The use of two multispectral remote sensing data sets to map and monitor IAPs in the Heuningnes Catchment, South Africa, was therefore investigated using the maximum likelihood classification algorithm. It was possible to identify areas infested with IAPs using remote sensing data. Specifically, IAPs were mapped with a higher overall accuracy of 71%, using Sentinel‐2 MSI as compared to using Landsat 8 OLI, which produced 63% accuracy. However, both sensors showed similar patterns in the spatial distribution of IAPs within the hillslopes and riparian zones of the catchment. This work demonstrates the utility of the two multispectral data sets in mapping and monitoring the occurrence and distribution of IAPs, which contributes to improved ecological modelling and thus to improved management of invasions and biodiversity in the catchment. Résumé: Les plantes étrangères envahissantes constituent une grave menace pour la biodiversité, le fonctionnement et les services de l'écosystème. La disponibilité de données satellite à résolution moyenne (ex. : Sentinel‐2 Multispectral Instrument et Landsat 8 Operational Land Imager) offre l'opportunité de cartographier et de contrôler l'apparition et la répartition spatiale des plantes étrangères envahissantes. L'utilisation de deux ensembles de données multispectrales obtenues par télédétection pour cartographier et contrôler les plantes étrangères envahissantes sur le bassin versant d'Heuningnes, en Afrique du Sud, a fait l'objet d'une étude en utilisant l'algorithme classification de vraisemblance maximale. L'identification des zones envahies par les plantes étrangères envahissantes a été rendue possible à l'aide de données obtenues par télédétection. Les plantes étrangères envahissantes ont notamment été cartographiées avec une précision d'ensemble plus élevée de 71, 03% à l'aide de Sentinel 2 MSI, en comparaison avec l'utilisation de Landsat 8, qui a permis d'atteindre une précision de 62, 95%. Cependant, les deux sondes ont montré des tendances similaires dans la répartition spatiale des plantes étrangères envahissantes sur les flancs des collines et dans les zones riveraines du bassin versant. Ce travail démontre l'utilité de deux ensembles de données multispectrales dans la cartographie et le contrôle de l'apparition et de la répartition des plantes étrangères envahissantes, ce qui contribue à l'amélioration de la modélisation écologique et donc de la gestion des invasions et de la biodiversité dans le bassin versant.